Assessing the selected heavy metals concentration on palm oil soil and fruit farm soil / Wan Noni Afida Ab Manan ... [et al.] - Ab Manan, Wan Noni Afida; Alias, Rubaiyah; Che Aziz, Nor Aimuni Syahirah; Laiman, Rusdin (2019)
This study was conducted at Felda Jengka 8, Pahang in Malaysia to find out the contents of heavy metals in palm oil soil and fruit farm soil adjacent to estimate the pollution level. Four types of selected heavy metals namely Cu, Zn, Pb and Ni in different soil sampling point were collected in triplicates and analysed by Inductively Coupled Plasma – Optical Emission Spectrometer (ICP-OES) after wet digestion. Contamination factor (CF) and geo-accumulation index (Igeo) were used to estimate the degree of contamination heavy metal in soil. Heavy metal concentration range were as follow; 0.910 – 2.000 mg/kg for Cu, 0.460 – 2.060 mg/kg for Zn, 0.080 – 0.220 mg/kg for Pb and 0.020 – 0.100 mg/kg for Ni. Cu and Zn concentration was found to be higher than other metal concentrations. The continuous application of chemical fertilizers possibly related to accumulation of heavy metals in soil. Results showed CF values were between moderate to considerable contaminant especially in palm oil soil. While, for Igeo values were indicated uncontaminated to fairly contaminated for the study sites. This recommends the utilization of chemical fertilizer is still in the monitoring. However, more physicochemical analyses are needed for metal analysis and determination of other heavy metal elements such as Cd, As, Se and Cr for further research.